L’impératif de « transition énergétique » comme double peine pour un territoire de la production énergétique soumis à reconversion - Joseph Cacciari (VertigO, 2014)
International political speeches on « energy transition » sometimes forget to see things from a ground level and to root their analyses on collective history. In order to reach the best balances, they set up goals which are related to changes in the way of living without taking into account how those changes happen. However, from a « bottom perspective », energy transition does not proceed from an homogeneous and automatic transposition of these goals. Moreover, in order to search social consequences of the past transformations in the energy mix, some social agents sometimes refer to past experiences. Then, they associate their conclusions with changes in the ways of living. Studding such a process at the scale of an area like Gardanne, in the mist of a former mining area in Provence (Bouche-du-Rhône, France), will allow us to grasp the energy transition from other perspectives. In fact, since the beginning of 1990, this city has anticipated the stop of the local coal extraction and has started a change in its energy model. One of the aspects of this anticipation is to be found both in the way people consume and in their behaviors towards energy. It also raises questions about the local cohesion, based on productive and symbolical dimensions related to energy. In this example, economic, symbolic and energy transitions are linked and can let us question the complexity of transformations in the social organization when those transformations are related to changes in the energy model. The article is based on a two-year survey, conducted in a local area, on different scales, in order to observe a current energy transition, from a perspective which is diachronic and synchronic.